Vaccine Hesitancy Is a Barrier to Achieving Equitable Herd Immunity Among Racial Minorities - Gerretsen, Philip; Kim, Julia; Quilty, Lena; Wells, Samantha; Brown, Eric E.; Agic, Branka; Pollock, Bruce G.; Graff-Guerrero, Ariel (Frontiers in Medicine, 2021)
Introduction: Racial minority groups have been disproportionately affected by the 2019 novel coronavirus disease (COVID-19). Vaccine hesitancy may be a major barrier to achieving equitable herd immunity and must be addressed to reduce the excess morbidity and mortality of COVID-19 in disproportionately affected communities. This study aimed to determine if COVID-19 vaccine hesitancy, and its factors vaccine complacency and confidence, is more prominent among disproportionately affected racial minority groups. Methods: We collected data from participants aged 18 years or older from the four most populous U.S. states, including New York, California, Florida, and Texas, and Canada. Data were collected using a web-based survey platform. Results: Data from 4434 participants were included (mean (SD) age=48.7(17.2) and 50.4% women). Vaccine hesitancy was higher in Black, Indigenous (Native American and Indigenous People of Canada including First Nations, Inuit or Métis), and Latinx compared to White participants, while no difference was found between East Asian and White participants. The group differences in vaccine hesitancy for Indigenous and Black compared to White participants remained after controlling for sociodemographic factors. Determinants of vaccine complacency were equivalent between disproportionately affected racial groups and white participants. Vaccine confidence (i.e., trust in vaccine benefit) was generally lower in all racial groups compared to White participants. Differences in vaccine mistrust comparing Black and East Asian to White participants remained after controlling for sociodemographic factors. Discussion: Public health and other relevant government services should address vaccine hesitancy among racial minorities using a culturally sensitive, community-centered approach to attain equitable herd immunity.